RETINAL LESION EVOLUTION IN SUSAC SYNDROME. Issue 2 (February 2016) - Brandt, Alexander U.; Oberwahrenbrock, Timm; Costello, Fiona; Fielden, Michael; Gertz, Karen; Kleffner, Ilka; Paul, Friedemann; Bergholz, Richard; Dörr, Jan
Abstract : Purpose: To describe retinal lesion development in Susac syndrome during acute, postacute, and late phases of the disease. Methods: Cross-sectional study of four patients with Susac syndrome and longitudinal short-interval case study of one additional patient. Retinal changes were analyzed with high-resolution spectral domain optical coherence tomography and retinal fluorescein angiography. Results: Retinal Susac syndrome lesions comprise four different lesion sections, which can be distinguished in acute and postacute phases of the disease: a primary section at the site of branch retinal artery occlusion, which spans more layers than supplied by the affected vessel; hypoxic sections from superficial and deep capillary networks; and an axonal damage section with degenerating axons from perished ganglion cells in the main and hypoxic sections. In the later stages, main and hypoxic lesion sections can no longer be distinguished, and both show degeneration from outer plexiform to retinal nerve fiber layers. Conclusion: The dynamics of lesion development and morphologically distinct lesion sections suggest more complex mechanisms of lesion evolution beyond an isolated endothelial immune reaction and subsequent hypoxic tissue damage. The characteristic lesion morphology assists in differentiating the diagnosis of acute visual loss in neuroinflammatory disease. Specificity of the identified changes has to be determined in future studies also including patients with other retinal vascular diseases. Abstract : Supplemental Digital Content is Available in the Text.This study describes the retinal lesion development in Susac syndrome during acute, postacute, and late phases of the disease using high-resolution optical coherence tomography, as well as identification and detailed description of four different lesion sections.